Warthin tumor of the oropharyngeal minor salivary gland. (December 2018) - Diaz-Segarra, Nicole; Young, Lauren K; Levin, Kristin; Rafferty, William; Brody, Joshua; Koshkareva, Yekaterina
Warthin tumor is the second most common benign salivary gland tumor that classically arises in the parotid gland. It can be synchronous, metachronous, multifocal, bilateral, or unilateral, which complicates diagnosis and management. Rare cases of Warthin tumor of the minor salivary gland are described, but no cases of unilateral, synchronous Warthin tumor involving the parotid and minor salivary gland have been reported. We present a case of Warthin tumor arising from a minor salivary gland in the left oropharynx of a 71-year-old male with a previous history of left parotid Warthin tumor, later determined to be synchronous.